(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
In order to give rise to new offspring, female body undergoes menstrual cycle. It involves the shedding of endometrium manifested as Māsānumāsika Rajaḥ Pravṛtti i.e., Ārtava Pravṛtti. Due to changes in life style of women in terms of Āhāra, Vihāra, there is more physical and emotional stress and this may result in Ārtavaduṣṭi, where the normal menstrual cycle gets disturbed or presented in altered form. Background: A married Hindu female patient of 35 years came to NIA Prasuti-stree Roga OPD on 25th July, 2019 with complaints of painful menstruation since last 14 years, heavy bleeding during menstruation since last 10 years and mild burning micturition with increased frequency of micturition (on/off) since last 2 years. Methodology: Mainly Pitta Doṣa vitiation symptoms were observed in the patient. Her complete Nidāna Parivarjana and Prakṛti Vighāta was done and Pitta Doṣa Śāmaka Dravyas were used in treatment including specific Pittaja Ārtavaduṣṭi line of treatment mentioned in Ayurvedic classics. She was given combination of Yaṣṭīmadhu Cūrṇa, Miśi (Fennel), Munakkā (dried Vitis vinifera), Goghṛta twice a day in the form of Kalka with warm water, Kuṭakī Cūrṇa, Munakkā, Dhāgā Miśrī in equal parts in the form of pea sized Guṭikā twice a day with cold water, Gokṣura Cūrṇa, Copcīnī Cūrṇa twice a day with water, Avipattikara Cūrṇa before meal, twice a day with water. The treatment was continued for 2 months. Result: There was relief in menstrual and urinary symptoms after 2 months of treatment.